Landing in affective atmospheres. (September 2022) - Preece, Chloe; Rodner, Victoria; Rojas-Gaviria, Pilar
Studies on affect and affective atmospheres have been a topic of increasing interest in marketing, particularly in the management of consumption and retail spaces where service providers attempt to orchestrate a prescribed, collective affective response in consumers. This paper draws on the work of Sara Ahmed and Margaret Wetherell to bring the subject back to the fore, providing a more fine-grained theorisation of how individuals land in such atmospheres. We articulate surfacing and sticking as key dimensions of landing, highlighting the heterogeneity of our landing, whereby affect is individually felt through bodily reactions due to how our personal affective history intersects with the socio-political context. Using a poetic affective attunement method, we capture intensely affective atmospheres, namely spirit-permeated religious settings in Brazil; demonstrating how landing results in different orientations or disorientations through which often elided emotional experiences come into view, privileging some subjects and objects whilst disadvantaging others.